Understanding German Grammar Through Reading Line Webtoon Digital Comics in Telegram Community - Kaffana Riski Audina; Aini, Desti Nur (Nexus Publishing NXP, 2025)
This study aims to describe German grammar learning through reading Webtoon and learners' responses in using Line Webtoon as a learning medium. The research subjects used were members of the telegram group